Metabolomics reveals the size effect of microplastics impeding membrane synthesis in rice cells - Zhenlong Yang; Xiao Xiao; Ting Liu; Haodong Wang; Xubiao Luo (Ecotoxicology and Environmental Safety)
The global-scale production of plastics has led to a significant accumulation in the environment, and it has become a major stressor to environmental sustainability, agricultural crops, and human health. Here we report the particle size effect of polystyrene (PS, typically microplastic) on the impact on rice suspension cells. This study used PS of different particle sizes (30 nm, 200 nm, and 2 μm) in a three-day co-culture experiment, the results showed that 30 nm, 200 nm, and 2 μm PS at the same concentration (100 μg/mL) caused 4.6 %, 55.8 %, and 66.4 % decrease in rice suspension cell viability, respectively. Furthermore, a substantial reduction in protein content, amounting to 26.53 % and 48.47 %, was observed in cells treated with 200 nm and 2 μm PS, and the DNA and RNA content of rice suspension cells also decreased substantially at 100 μg/mL PS. Non-targeted metabolomics analyses showed that PS disrupted fatty acid biosynthesis with a clear size effect, wherein 2 μm PS caused a decrease of 64.9 % in hexadecanoic acid content. Consequently, this finding provides valuable perspectives on the potential ecotoxicity of microplastics at the single-cell level of rice and will facilitate the formulation of an environmental management program specifically tailored for addressing the challenges posed by microplastics.